Surface urban heat island effect and its spatiotemporal dynamics in metropolitan area: a case study in the Zhengzhou metropolitan area, China - Meng, Fei; Yan, Shuling; Tian, Guanghui; Wang, Yudong (Frontiers in Environmental Science, 2023)
The deterioration of the urban surface thermal environment has seriously affected regional environments and human health, becoming a critical ecological problem faced by cities worldwide. This study focused on surface urban heat island effect in metropolitan area and selected the emerging metropolitan area of Zhengzhou, China, as a case study. Based on the MODIS land surface temperature data obtained from the Google Earth Engine (GEE), the surface urban heat island intensity (SUHII) was calculated and its temporal and spatial dynamics were analyzed from 2003 to 2022. The main findings indicated that Zhengzhou, the core city of the metropolitan area, had the strongest urban heat island effect with day SUHII of 1.10℃ and night SUHII of 1.39℃). Generally, the average annual SUHII was higher during the day than at night, and the maximum value was detected in summer (2.43℃). SUHII showed an increasing trend at night, especially in summer during the study period. It decreased obviously in urban centers during the day, while it increased obviously in the outer urban areas at night. The results of this study contributed to the understanding of the spatiotemporal dynamics of the urban heat island effect in the Zhengzhou metropolitan area.